THE INFLUENCE OF PERCEIVED QUALITY, BRAND IMAGE, AND EMOTIONAL VALUE TOWARDS PURCHASE INTENTION OF CONSINA BACKPACK - Saidani, Basrah; Muztahid, Muh. Sifaul; Haro, Andrian (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
This study was conducted to determine the descriptive and empirical impact of perceived quality, brand image and emotional value toward purchase intention. The object of this research was respondents of backpack users in East Jakarta. Methods of data collection using survey methods. Data analysis using SPSS to process and analyze the research data. The results of descriptive test explained that perceived quality, brand image and emotional value of backpack Consina is good according most respondents answer, so they have quite high purchase intention. The hypothesis test shows, perceived quality has positive and significant effect on purchase intention, brand image has positive and significant effect on purchase intention, emotional value has positive and significant effect on purchase intention, perceived quality, brand image and emotional value have simultaneous effect on purchase intention. Keywords: Perceived Quality, Brand Image, Emotional Value, Purchase Intention